Awareness of Medical Professionals about Common Disinfectants in a Tertiary Care Hospital Against Corona Virus - Fahim, Qanita; Shah Bukhari, Karamat Hussain; Khattak, Abdul Katif; Uddin, Nasir; Sattar, Nadia; Malik, Nasir Javed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess the working knowledge of health care workers (HCW) regarding the appropriate use of disinfectants against Coronavirus in hospital care settings using a questionnaire.Study Design: Cross-sectional study.Place and Duration of Study: Combined Military Hospital Lahore, Pakistan, from Apr 2020.Methodology: Two hundred health care workers were consecutively selected and divided into two groups, irrespective of gender. Each participant had to fill a structured proforma containing twenty-five close-ended questions.Result: Group-1 participants were 126 (63%) and group 2 participants were 74 (37%). 117 (92.8%) group-1 participants were 20–30 years of age and degree holders while 40 (54%) group-2 participants were 31-40 years old and diploma holders. Significant awareness (p10 years were the high achievers in both groups.Conclusion: This study revealed that majority of the participants knew about the correct usage of disinfectants and they were fully prepared to handle the ongoing pandemic. Another finding was that awareness was directly related to relevant education, prolonged work experience and age